Design of Sb2Te3 nanoblades serialized by Te nanowires for a low-temperature near-infrared photodetector - Yin, Hong; Li, Huaiyu; Yu, Xiang-xiang; Cao, Minglei (Frontiers in Chemistry, 2022)
The dangling bond on the surface of bulk materials makes it difficult for a physically contacted heterojunction to form an ideal contact. Thus, periodic epitaxial junctions based on Sb2Te3 nanoblades serialized by Te nanowires (Sb2Te3/Te) were fabricated using a one-step hydrothermal epitaxial growth method. X-ray diffraction and electron microscopy reveal that the as-prepared product has a good crystal shape and heterojunction construction, which are beneficial for a fast photoresponse due to the efficient separation of photogenerated carriers. When the Sb2Te3/Te composite is denoted as a photodetector, it shows superior light response performance. Electrical analysis showed that the photocurrent of the as-fabricated device declined with temperatures rising from 10K to 300K at 980 nm. The responsivity and detectivity were 9.5 × 1011 μA W−1 and 1.22 × 1011 Jones at 50 K, respectively, which shows better detection performance than those of other Te-based photodetector devices. Results suggest that the as-constructed near-infrared photodetector may exhibit prospective application in low-temperature photodetector devices.